-4=-2w-7

Simple and best practice solution for -4=-2w-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4=-2w-7 equation:


Simplifying
-4 = -2w + -7

Reorder the terms:
-4 = -7 + -2w

Solving
-4 = -7 + -2w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '2w' to each side of the equation.
-4 + 2w = -7 + -2w + 2w

Combine like terms: -2w + 2w = 0
-4 + 2w = -7 + 0
-4 + 2w = -7

Add '4' to each side of the equation.
-4 + 4 + 2w = -7 + 4

Combine like terms: -4 + 4 = 0
0 + 2w = -7 + 4
2w = -7 + 4

Combine like terms: -7 + 4 = -3
2w = -3

Divide each side by '2'.
w = -1.5

Simplifying
w = -1.5

See similar equations:

| 8w+3=5w-18 | | 4x+1+19x=11 | | 6m+8=2m-12 | | 9t-7=3t-5 | | 20y-6=18y+4 | | 4(6a+2)=-88 | | -2(3s-3)-6=-3(6s+0)-5 | | 3(-6t+4)=-5t+2(t-9) | | 14+b=13-3b | | 12x^4=2x^2+4 | | 2ysquare=12y-5y | | 4y+3=127 | | X^2-9y^2+6x-36y-36=0 | | 10=(6+9b)+7b | | 3log(2)=9log(x) | | x+6=4x-21 | | 6x+8+2x+4= | | 5.36-0.4m=26.8-0.4m | | 3(4x+3)+4x=61 | | (35-2x)(70-2x)= | | Y^2=2px+p^2 | | 13x+2=13x-4 | | (x-b)=x | | 2x-5/7=8/25 | | x+(-16)=-12 | | nx=3y-5 | | 2/3(m-8)=9 | | 35=3x+2(x-5) | | 24000/X=0 | | 0.2x-3.4=0.5x-2.5 | | 6=1-3p | | 130=24x+2 |

Equations solver categories